Association of Diabetic Retinopathy With Stroke: A Systematic Review and Meta-Analysis - Hu, Kaiyan; Jiang, Mengyao; Zhou, Qi; Zeng, Weiting; Lan, Xuhong; Gao, Qianqian; Mei, Fan; Zhao, Li; Chen, Fei; Wu, Anhu; Tao, Gongcai; Mou, Chenghua; et al. (Frontiers in Neurology, 2021)
Background: The population-based studies conducted thus far do not provide conclusive evidence of the link between diabetic retinopathy (DR) and stroke. The aim of the present systematic review was to determine whether DR is specifically associated with stroke. Methods: MEDLINE, Embase, and Web of Science were systematically searched from their inception to July 31, 2020. All cohort studies that reported associations between the presence of DR and incident stroke were included. The pooled hazard ratios (HRs), pooled risk ratios (RRs), and 95% confidence intervals (CIs) were calculated. Results: The meta-analysis included 19 cohort studies involving 81,452 diabetic patients. The pooled effect size of any DR related to stroke was 1.25 for HR (95% CI: 1.12-1.39; P<0.0001) and 1.96 for RR (95% CI: 1.60-2.39; P<0.0001). Subgroup analysis for the type of diabetes yielded pooled HR of 1.29 (95% CI 1.10–1.50; P = 0.001) in patients with T2DM. The pooled RR was 2.29 (95% CI 1.77–2.96; P<0.0001) in patients with T2DM. Two studies addressed the DR-related stroke among T1DM patients. One study found a significant association between DR and stroke (OR: 1.6; 95% CI: 1.1-2.3; P<0.01), while the other did not identify an association between these two conditions (RR: 1.40; 95% CI: 0.62-2.18; P=0.178). Conclusions: The presence of DR is associated with an increased risk of stroke in diabetic patients. This correlation is robust in T2DM patients but uncertain in T1DM patients. Our findings indicate that DR is an important biomarker for the prediction of stroke. To further validate the role of DR in stroke-risk stratification, additional research is required on the association between the stage of DR and stroke risk, and more studies including T1DM patients are necessary.